Oral rinse as a potential method to culture Candida isolate from AIDS patients - Desiana Radithia; Hening T. Hendarti; Bagus Soebadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Candida isolate is easily sampled from oral cavity by swabbing directly on the candidiasis lesion, to be smeared onto slides for direct examination or cultured in a growth medium. This method is by far the gold standard for defining candidiasis diagnosis. However it is difficult to apply on sensitive patients and almost impossible on patients showing no clinical appearance of oral candidiasis. AIDS patients are very prone to candida infection and have a tendency of repetitive infection involving mixed species. As many candida species show different susceptibility to anti-fungal agents, it is necessary to identify the species causing the infection in the management of oral candidiasis. Oral rinse is a suggested method to obtain candida isolate to be cultured for further analysis such as species identification. This method is simple and less risky on infection transmission as less tools are required in the procedure. Purpose: This study aimed to assess the application of oral rinse as an alternative method to culture Candida isolate from AIDS patients. Methods: A cross-sectional observative study was conducted in HIV/AIDS in-Patient Facility of Intermediate Care Unit for Infection Disease, Dr. Soetomo Hospital Surabaya. Fourteen stadium 4 AIDS patients matching criteria were swabbed on 1/3-posterior of the tongue, and then given 10 ml phosphate buffer saline to rinse vigorously for 15 seconds. Both specimens were cultured on Sabouraud’s dextrose agar and colony growth was observed. Results: Candida colonies were able to grow from all 14 isolates (100%) by both methods. Qualitatively, cultures from oral rinse specimens were more populated than cultures from swab specimens. Conclusion: Oral rinse is an applicable technique to obtain Candida species isolate. This technique is safe, easy, non-invasive, and needs less tools therefore less risky for HIV transmission.Latar belakang: Isolat Candida mudah diambil dengan cara mengusap lesi candidiasis, baik untuk dioleskan pada kaca preparat untuk pemeriksaan langsung maupun dikultur. Hingga kini, metode tersebut dinyatakan sebagai “standar emas” untuk menentukan diagnosis. Namun kekurangan metode ini yaitu berisiko merangsang muntah pada pasien sensitif, dan hanya bisa dilakukan bila tampak jelas ada lesi. Candidiasis adalah penyakit nosokomial yang sering terjadi. Pasien AIDS sangat rentan terhadap infeksi oportunis ini secara rekuren dan persisten. Identifikasi spesies penyebab harus dilakukan karena berbagai spesies Candida memiliki kerentanan yang berbeda terhadap berbagai jenis antifungal. Oral rinse adalah metode pengambilan isolat Candida yang non-invasif. Isolat yang didapat bisa dikultur dan diidentifikasi, selain itu bisa dilakukan pada pasien yang belum menunjukkan adanya lesi candidiasis untuk menentukan besar risiko pasien terkena candidiasis, sehingga dapat ditentukan perlu tidaknya pemberian profilaksis antifungal. Tujuan: Penelitian ini bertujuan mengamati efektivitas metode oral rinse untuk mengisolasi Candida dari rongga mulut pasien AIDS. Metode: Penelitian observasional dilakukan di bagian Rawat Inap Unit Perawatan Intermediate Penyakit Infeksi RSUD Dr. Soetomo. Swab pada 1/3 posterior lidah dilakukan pada 14 pasien yang memenuhi kriteria, kemudia pasien diberi 10 ml phosphate buffer saline untuk berkumur kuat-kuat selama 15 detik. Spesimen yang didapat melalui kedua metode dikultur pada medium Sabouraud untuk diamati. Hasil: Koloni Candida berhasil dikultur dari 14 spesimen (100 %) melalui kedua metode isolasi. Secara kualitiatif tampak bahwa hasil kultur dari oral rinse tampak lebih subur. Kesimpulan: Oral rinse adalah metode yang dapat diaplikasikan untuk mengisolasi Candida dari rongga mulut pasien. Tekniknya mudah, aman, non-onvasif, dan tidak memerlukan peralatan dan ketrampilan khusus, sehingga mengurangi risiko transmisi HIV.